Rheum moorcroftianum (Polygonaceae) in Kashmir Himalaya - Khan, Mohd. Ishfaq; Pandith, Shahzad A.; Ramazan, Salika; Shah, Manzoor A.; Malik, Akhtar H.; Reshi, Zafar A. (Phytotaxa, 2019)
Rheum moorcroftianum (Polygonaceae) was recorded for the first time in Kashmir Himalayas region. The species was identified using morphological and molecular (DNA-barcode) data. R. moorcroftianum can be distinguished from the other Rheum species on the basis of absence of stem, 3‒7 or more basal leaves, inflorescence in branched panicle, rachis papilliferous, perianth yellow-white, anthers pinkish-red, and seeds red, 3-winged.